Evaluating Green Efficiency of Manufacture Sector and Its Determinants in East Java Province - Iqram Ramadhan Jamil; Ananda Sintia Putri; Nur Azizah Arianggi Suryaatmaja (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
East Java is one of the provinces in Indonesia that carries out intensive development in the industrial sector to improve the welfare of its society. However, massive industrial activity will pose its challenges, such as increased emissions and environmental degradation. This study aims to determine the manufacturing sub-sector that produces CO2 emissions and has the lowest green efficiency as well as its determinant variables. There are three stages of analysis applied in this research i.e. carbon emission measurement, Slack Based Measurement-Data Envelopment Analysis (SBM-DEA), and Tobit regression. The study use 5-digit manufacturing subsector data based on the International Standard Industrial Classification (ISIC) system, obtained from the Indonesian Central Agency of Statistics (BPS) which is deflated against the East Java Regional Gross Domestic Product (GRDP) deflator with 2010 as the base year. The results of the analysis show that in general, the manufacturing subsector in East Java produces quite high CO2 emissions of 85.28 tons. The subsector with the highest average CO2 emissions in East Java in 2017 was the fertilizer industry, in 2018 the non-ferrous base metal manufacturing industry, and in 2019 the steel rolling industry. Then, the drying industry and tobacco depreciation became the sub-sector with the lowest average green efficiency in East Java Province in 2017. Meanwhile, in 2018 it was the milling industry of various nuts (including Leguminous) and in 2019 it was the coffee processing industry. The Tobit regression results show that the energy structure and industrial concentration have no significant effect on the green efficiency value of the manufacturing subsector. Meanwhile, spending on R&D has a significant negative effect on green efficiency. Therefore, the recommendations given are encourage the use of environmentally friendly raw materials and fuels, increasing green innovation, and increasing consumer awareness regarding environmental issues.